2020
DOI: 10.5005/jp-journals-10071-23615
|View full text |Cite
|
Sign up to set email alerts
|

Complications after Supramajor Gastrointestinal Surgery: Role of Enhanced Recovery after Surgery

Abstract: A bstract Background Enhanced recovery after surgery (ERAS) is currently the standard of care in perioperative medicine, but it is widely underutilized in our healthcare setting because of the lack of awareness of benefits exerted by ERAS and its components. ERAS is a multidisciplinary collaboration, where intensivists play an important role in the implementation of the protocol during the perioperative period. Aim This review article aims to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The different incidence of pneumonia between robotic and laparoscopic approaches could be explained by the lower pneumoperitoneum pressure of robotic surgery with a consequent lower extent of lung atelectasis [ 47 ]; indeed, the increasing of intrabdominal pressure due to carbon dioxide insufflation not only causes the lifting of diaphragm but also the increase in lung resistance and a rise in thoracic pressure with an augmented risk of pulmonary aspiration and hypoxemia [ 47 ]. Notably, other crucial risk factors for post-operative pulmonary complications are strictly related to the anesthesia management; for instance, a high concentration of inspired oxygen, an inappropriate neuromuscular blockade, and different ventilation strategies could lead to an augmented incidence of post-operative respiratory issues: more studies are needed to clarify the different contributions of anesthesia and surgery related factors to pulmonary complications [ 7 , 47 , 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The different incidence of pneumonia between robotic and laparoscopic approaches could be explained by the lower pneumoperitoneum pressure of robotic surgery with a consequent lower extent of lung atelectasis [ 47 ]; indeed, the increasing of intrabdominal pressure due to carbon dioxide insufflation not only causes the lifting of diaphragm but also the increase in lung resistance and a rise in thoracic pressure with an augmented risk of pulmonary aspiration and hypoxemia [ 47 ]. Notably, other crucial risk factors for post-operative pulmonary complications are strictly related to the anesthesia management; for instance, a high concentration of inspired oxygen, an inappropriate neuromuscular blockade, and different ventilation strategies could lead to an augmented incidence of post-operative respiratory issues: more studies are needed to clarify the different contributions of anesthesia and surgery related factors to pulmonary complications [ 7 , 47 , 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the last 50 years, the use of minimally invasive surgery spread all over the world, and video-laparoscopic-assisted surgery became a common technique; a recent study reported that the average number of the laparoscopic abdominal GI procedures performed by residents increased considerably in the last decades [ 6 ]. Even if laparoscopic-assisted surgery largely demonstrated its advantages, the incidence of complications (i.e., pneumonia, ICU recovery, stroke, acute kidney failure, cardiac arrest, anastomotic leakage, deep vein thrombosis, and other respiratory or cardiovascular complications) in major GI surgery remained high (33–44%), thus worsening the prognosis and the quality of life of the patients and increasing the length of hospitalization and the healthcare-related costs [ 7 , 8 , 9 ]. The wide diffusion of laparoscopic systems was probably due to the relative low costs of the system (about 1000£/patient for disposables and about 90£/patient for system) that seems to be well balanced by the several advantages of this technique [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The nature of surgical complications presents another unique challenge. Acute postoperative surgical complications include general complications such as sepsis and myocardial infarction, as well as procedure-specific complications like anastomotic leak after colorectal surgery or duodenal stump leak after gastrectomy—events that are low frequency but potentially catastrophic and time-sensitive when they occur 24 , 25 . Prediction of rare clinical events presents the risk of alert fatigue and wasted resources if a model flags too many false positives, and unnecessary excess morbidity and mortality for a model with too many false negatives.…”
Section: Clinical Risk Predictionmentioning
confidence: 99%